A review on the effect of increasing temperature on paddy reproductive phase / Mohammad Ansarullah Mohd Taufek - Mohd Taufek, Mohammad Ansarullah (Faculty of Plantation and Agrotechnology, 2018)
Extreme weather condition phenomenon and global warming will decrease the rice paddy yield and can affect the global economy because rice is one of the most consumed crops in the world especially in Asia. It is essential to study the production of rice in relation to the current climate and to make an estimation of the response of rice yield changes to climactic factors such as temperature, rainfall and photoperiod of crop. The best optimum temperature for growth of rice is in range between 20-35ºC and minimum temperature 22-24ºC. Rice is extremely sensitive to short duration heat stress episodes at above 35ºC during the anthesis in reproductive stage. Climate change is recognized to increase the frequency and severity of extreme temperature events. Prices of agricultural commodities are predicted to increase by 40% with a global temperature increase of 3°C. Increase in prices resulted from increases of input required to overcome the challenges resulting from effect of heat stress to the global agriculture production which also includes rice.